Frontotemporal dementia non-sense mutation of progranulin rescued by aminoglycosides. (8th January 2020) - Kuang, Lisha; Hashimoto, Kei; Huang, Eric J; Gentry, Matthew S; Zhu, Haining
Abstract: Frontotemporal dementia (FTD) is an early onset dementia characterized by progressive atrophy of the frontal and/or temporal lobes. FTD is highly heritable with mutations in progranulin accounting for 5–26% of cases in different populations. Progranulin is involved in endocytosis, secretion and lysosomal processes, but its functions under physiological and pathological conditions remains to be defined. Many FTD-causing non-sense progranulin mutations contain a premature termination codon (PTC), thus progranulin haploinsufficiency has been proposed as a major disease mechanism. Currently, there is no effective FTD treatment or therapy. Aminoglycosides are a class of antibiotics that possess a less-known function to induce eukaryotic ribosomal readthrough of PTCs to produce a full-length protein. The aminoglycoside-induced readthrough strategy has been utilized to treat multiple human diseases caused by PTCs. In this study, we tested the only clinically approved readthrough small molecule PTC124 and 11 aminoglycosides in a cell culture system on four PTCs responsible for FTD or a related neurodegenerative disease amyotrophic lateral sclerosis. We found that the aminoglycosides G418 and gentamicin rescued the expression of the progranulin R493X mutation. G418 was more effective than gentamicin ( 50% rescue versus <10%), and the effect was dose- and time-dependent. The progranulin readthrough protein displayed similar subcellular localization as the wild-type progranulin protein. These data provide an exciting proof-of-concept that aminoglycosides or other readthrough-promoting compounds are a therapeutic avenue for familial FTD caused by progranulin PTC mutations.